Stability of Non-Hyperbolic Equilibrium Point for Polynomial System of Differential Equations - Vahidin Hadžiabdić (TEM Journal, 2021)
In this paper, a polynomial system of plane differential equations is observed. The stability of the non-hyperbolic equilibrium point was analyzed using normal forms. The nonlinear part of the differential equation system is simplified to the maximum. Two nonlinear transformations were used to simplify first the quadratic and then the cubic part of the system of equations.